Helicobacter pylori-Specific CD4⁺ T Cells Home to and Accumulate in the Human Helicobacter pylori-Infected Gastric Mucosa - Lundgren, Anna; Trollmo, Christina; Edebo, Anders; Svennerholm, Ann-Mari; Lundin, B. Samuel (Infection and Immunity, 2005)
Helicobacter pylori infects the stomach and duodenal mucosa. T cells are important components of the H. pylori-induced immune response, but little is currently known about how these cells are recruited to the infected mucosa. Here, we have characterized stomach and duodenal T cells isolated from H. pylori-infected and noninfected subjects with regard to subtype, expression of homing and chemokine receptors, and in vitro reactivity to H. pylori antigens. Higher numbers of CD4⁺ but similar numbers of CD8⁺ lamina propria T cells were isolated from stomach biopsies from H. pylori-positive compared to H. pylori-negative individuals. CD4⁺ T cells from infected stomach expressed increased levels of the homing receptor L-selectin and the chemokine receptor CCR4 compared to CD4⁺ T cells from uninfected stomach. Infected stomach mucosa also contained increased levels of the CCR4 chemokine ligand MDC/CCL22. In contrast, comparable numbers of CD4⁺ T cells with similar receptor expression were isolated from the duodenum of H. pylori-positive and H. pylori-negative individuals. In vitro proliferation of mucosal T cells was strongly enhanced by the addition of interleukin-2 (IL-2) and IL-7 to the cell cultures. Using this approach, H. pylori-specific T-cell responses were detected in stomach CD4⁺ T cells from H. pylori-positive but not H. pylori-negative individuals. Duodenal T cells from only a few individuals responded to H. pylori stimulation, and the responsiveness was not restricted to H. pylori-positive individuals, suggesting limited H. pylori specificity in the duodenum and possible cross-reactivity with antigens from other bacteria in this compartment. In conclusion, these results suggest that H. pylori-specific CD4⁺ T cells preferentially home to and accumulate in the infected stomach and that L-selectin and CCR4/MDC are important for this recruitment.